VALIDITAS DAN KEPRAKTISAN MODUL PRAKTIKUM DIGITAL BERBASIS FLIPBOOK DALAM MATA KULIAH PENDALAMAN MATERI IPA SD - Mega Laeni; Yona Wahyuningsih; Dede Margo Irianto; Tita Mulyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science Material Deepening is one of the courses in the Elementary School Teacher Education Study Program (PGSD) at the Indonesian University of Education Campus in Cibiru. Practical activities play an important role in the learning process in this course. However, the implementation of practicums still faces a major obstacle, namely the lack of a practicum module specifically designed to support learning activities systematically and integrated. This study aims to analyze the validity and practicality of a Flipbook-based digital practicum module developed for the Elementary School Science Material Deepening course. The research method used is Research and Development (R&D) with the Alessi and Trollip development model, which consists of three main stages: planning, design, and development. Data collection techniques were carried out through two types of questionnaires. The module validation questionnaire was given to material and media expert validators and the module practicality questionnaire was tested on PGSD students after the trial. The results of the study indicate that the Flipbook-based digital practicum module has a high level of validity based on the assessment of material and media experts. The validity score from the material experts based on Aiken's V reached an average of 0.93, while the validity score from the media experts was 0.8. Furthermore, the beta test results showed that the module received an average rating of 3.7, which is categorized as very practical. Thus, this flipbook-based digital practicum module developed using the Alessi and Trollip model has proven valid and practical, and is suitable for use as teaching material in the Elementary Science Material Deepening course